Market Segmentation of the Brazilian Aluminum Industry: A Proposition of a Step-by-step Structure - de Moraes, Claudio Alberto; Mattar, Fauze Najib (Organizações & Sociedade, 2014)
This current paper presents a proposition of a step-by-step structure to the segmentation of business to business markets. This has been developed from extensive exploratory research and encompasses four major groups and a total of fourteen steps. Its characteristics make it a logic and useful structure that can be applied in a variety of industries and consumer markets. The segmentation studied that led to its development was that related to the sought benefits by the consumers of the aluminum industry. This industry presents some important features that posed new challenges to the present study: it is characterized as an oligopoly and its product is classified as a commodity with its price being set by the LME, being very close to a market structure of perfect competition. In this sense, the market segmentation becomes the main alternative to shift it to an imperfect competition. The exploratory research has identified that the aluminum industry practices some incipient kind on market segmentation that just provides pos-facto information for comparisons within the industry. Based on the data gathered through an empiric research, seven sought benefits were identified through factorial analysis: delivery effectiveness, technical and sales qualification, loyalty and relationship with the suppliers, image of the supplier, direct sales by competitive prices, product efficiency and logistics of the product and scrap.